ADVANTAGES AND LIMITATIONS IN IMPLEMENTATION OF BUSINESS INTELLIGENCE SYSTEM IN MONTENEGRO: CASE STUDY TELENOR MONTENEGRO - Ljiljana Kašćelan (Economic Review)
Data warehouse is the main technology which integrates data from company operations. Business Intelligence with DW at its center, enables the company to extract very important information for making business decisions from these data. Implementation of these systems is a very expensive and long lasting process. These systems are used a lot and they bring great benefits to companies in developed economies. However, their implementation has a great number of limitations, especially in our conditions of operations. In this paper we have recognized the advantages and limitations of implementation of the BI systems in poor conditions of operations and on a small market such as the one in Montenegro, as well as the methods for overcoming some of those limitations. We have also done the case study research which shows that the implementation of these systems is possible even under such circumstances.